7(2m-1)-(3/5)m=6/5(4-3m)

Simple and best practice solution for 7(2m-1)-(3/5)m=6/5(4-3m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2m-1)-(3/5)m=6/5(4-3m) equation:



7(2m-1)-(3/5)m=6/5(4-3m)
We move all terms to the left:
7(2m-1)-(3/5)m-(6/5(4-3m))=0
Domain of the equation: 5)m!=0
m!=0/1
m!=0
m∈R
Domain of the equation: 5(4-3m))!=0
m∈R
We add all the numbers together, and all the variables
7(2m-1)-(+3/5)m-(6/5(-3m+4))=0
We multiply parentheses
-3m^2+14m-(6/5(-3m+4))-7=0
We multiply all the terms by the denominator
-3m^2*5(-3m+4))+14m*5(-3m-3m+4))-(6-7*5(+4))=0
We add all the numbers together, and all the variables
-3m^2*5(-3m+4))+14m*5(-6m+4))-(6-7*54)=0
We add all the numbers together, and all the variables
-3m^2*5(-3m+4))+14m*5(-6m=0
Wy multiply elements
-75m^4(--6m=0
We do not support empression: m^4(

See similar equations:

| (Xx2)+125=2059 | | 3r^2-3r+1=37 | | x^2-20x+181=0 | | 31-(2x+9)=2(x+6)+x | | 1+4x-8=0 | | 8a-(4a-3)=1 | | 12x-18+8x-12+x=180 | | 32=9/4x | | 42=x-19 | | 1/6x+3/2=-1/3 | | 6(x-6)+2=8(x+20-6 | | 3/11=x/x+9 | | (x-2)(x-5)=8 | | 1/4x=116 | | .2-1x+2.5=-3.6 | | a^2+(2a)^2=400 | | 13.5x=-7+94.5 | | 6x=19,5 | | 4y-3+y+33=7y+30-5y | | -8+3=-24+13x | | 4y-10+y+56=5y=50-2y | | 3v^+18v=0 | | -5(0.1x+0.2)-0.6=-0.1 | | 1.8x+3.6=6-4x+15 | | 2x=19/2 | | (6+u)(5u+9)=0 | | 883.39/1,257,521=x/1,007,369 | | 2(5x+20)=6(2x=4) | | 10x+8=9x+1 | | 8(8n+4)=4(-7n+8) | | 4m+3=23;6 | | y/3+4=5/3 |

Equations solver categories